(untitled) (Research, Society and Development, 2021)
Agribusiness is a prime sector for the economy of Brazil, with the state of Goiás as one of its protagonists. In measuring the participation related to agriculture and livestock, it is more expressive with a 37.48% share in the composition of the GDP agribusiness agro-industrial complex of Goiás. This active performance represents the urban sectors and their link with the sectors of the state economy. This data disaggregated, livestock has a 38.67% share in the total, while agriculture has 61.33%. Of the total state GDP, the relative value of 27.60% is the GDP share of agribusiness. The use of the input-output matrix with the compilation of the added values at consumer prices made it possible to also analyze in detail the inputs, agribusiness and agri-services. The latter accounted for 27.74% of the state’s agribusiness GDP calculated. The dynamics found shows the degree of dependence on the state and national economy for each of the economic aggregates analyzed.